The deep space galactic cosmic ray lineal energy spectrum at solar minimum. Issue 6 (18th June 2013) - Case, A. W.; Kasper, J. C.; Spence, H. E.; Zeitlin, C. J.; Looper, M. D.; Golightly, M. J.; Schwadron, N. A.; Townsend, L. W.; Mazur, J. E.; Blake, J. B.; Iwata, Y.
Abstract : [1] The Cosmic Ray Telescope for the Effects of Radiation (CRaTER) instrument is an energetic particle telescope on board the Lunar Reconnaissance Orbiter spacecraft. CRaTER measures energetic charged particles that have sufficient energy to penetrate the outer shielding of the instrument (about 12 MeV/nucleon). Galactic cosmic rays (GCR) with these energies are the primary radiation concern for spacecraft and astronauts outside of the Earth's magnetosphere during times of minimal solar activity. These particles can easily penetrate typical shielding and damage electronics, causing increased electronics failure rates and single event upsets. When this radiation impacts biological cells, it causes an increased risk of cancer. The CRaTER instrument was built to characterize the radiation dose and lineal energy with unprecedented time and energy resolution and was fortuitously flown during a period of time that coincided with the highest GCR fluxes in the modern space age. We report here this worst‐case GCR lineal energy spectrum. Observations are made behind a thin aluminum window and different thicknesses of tissue‐equivalent plastic. These measurements provide important observational data points to compare with current model predictions of the dose deposited by energetic particles within a tissue‐like material. Key Points: GCR measured by CRaTER during highest flux in space age Lineal energy spectra are presented from solar minimum Lineal energy spectra provide basis for detailed transport modeling